The impact of psychiatric comorbidities on the length of hospital stay in patients with heart failure. (15th March 2016) - Carter, Paul; Reynolds, Jennifer; Carter, Andrew; Potluri, Siri; Uppal, Hardeep; Chandran, Suresh; Potluri, Rahul
Abstract: Background: Heart failure (HF) is a major healthcare problem contributing significantly to hospital admission stays and National Health Service (NHS) spending. Reducing length of hospital stay (LoS) in HF is paramount in reducing this burden and is influenced by factors relating to the condition, sociodemographics and comorbidities. Psychiatric comorbidities are being increasingly identified amongst HF patients but their impact on LoS has not been studied in the UK. Methods: We investigated the impact of psychiatric comorbidities on LoS amongst 31, 760 HF patients admitted to hospitals in North England between 1st January 2000 and 31st March 2013 from the ACALM (Algorithm for Comorbidities, Associations, Length of stay and Mortality) study. The ACALM protocol uses ICD-10 and OPCS-4 coding to trace HF patients, psychiatric comorbidities and demographics including LoS. Results: Amongst 31, 760 HF patients mean LoS in the absence of psychiatric comorbidities was 11.2 days. The presence of a psychiatric comorbidity increased LoS by 3.3 days. Logistic regression accounting for age, gender and ethnicity showed that LoS was significantly longer in patients suffering from depression (3.4 days, p < 0.001), bipolar disorder (8.8 days, p < 0.001) and all types of dementia (4.2 days, p < 0.001). Conclusions: Our results demonstrate that psychiatric comorbidities have a significant and clinically important impact on LoS in HF patients in the UK. Clinicians should be actively aware of psychiatric conditions amongst HF patients and manage them to reduce LoS and ultimately the risk for patients and financial burden for the NHS.